Muslim Millennial’s Buying Behavior of Halal Food & Beverage in Indonesia: The Mediating Effect of Purchase Intention - Fadillah, Hikmatul Nur; Ridlwan, Ahmad Ajib; Suryaningsih, Sri Abidah; Indrarini, Rachma (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
This study aims to determine the factors that influence consumer behavior in buying halal food and beverages in Indonesia for the millennial generation. These factors include halal awareness, halal certification and attitudes which are important factors in influencing buying behavior directly or through buying intention as a mediating/intervening variable. Data collection was carried out through a questionnaire with a total of 206 millennial Muslims who consume the halal product in Indonesia and also part of society with births in late 1980 to early 2000 using non-probability sampling. To assist in data analysis using sem-pls with PLS-4 application. The results of the study show that there is a relationship between halal awareness, halal certification and attitudes towards consumer buying behavior which is mediated by purchase intention. In addition, for a direct relationship between halal certification and attitudes toward buying behavior, a positive and significant effect was found. Interestingly, it was found that halal awareness has no significant effect on consumer buying behavior. This study can be used also by companies and for marketing discussions to develop halal food and beverage products for Muslim consumers in Indonesia.